(untitled) (Journal of Asian Development Studies, 2023)
Tent Pegging sport in Pakistan is not only a display of prowess, but to the nation, it is a living testament due to its connectivity with its historical past. This article aims to apprise, edify and engross readers about tent pegging and concisely introduce its origin, history, cultural implications, and significance. It personifies the sportsmanship, spirit of unity, linguistic, geographical and cultural divides. Pakistani culture is bonded through the Tent Pegging in a shared skill, spirit of competition and same appreciation for its tradition in the region. Tent Pegging is a platform for nurturing the talents of Pakistani youth and is now a source of inspiration for all. The rider’s dedication is to preserve the tradition and advance Tent Pegging throughout the region through organizing events and competitions. As a result, their hard work assists as an inspiration, encouragement and beacon for future generations of the area. Looking ahead, it is domineering that we constantly support and celebrate this sport in Pakistan. This entails devoting to facilities, endorsing awareness and providing opportunities for young players and riders to sharpen and hone their skills.